Ultraporous nitrogen-doped zeolite-templated carbon for high power density aqueous-based supercapacitors. (April 2018) - Mostazo-López, María José; Ruiz-Rosas, Ramiro; Castro-Muñiz, Alberto; Nishihara, Hirotomo; Kyotani, Takashi; Morallón, Emilia; Cazorla-Amorós, Diego
Abstract: Two zeolite templated carbons (ZTC) with comparable structure and different surface chemistry have been synthesized by chemical vapor deposition of different precursors, producing a non-doped and a N-doped carbon material (4 at. % XPS) in which most of the functionalities are quaternary N. A larger specific capacitance (farads per surface area) has been measured in acid electrolyte for the N-doped ZTC, that can be related to an improved wettability due to the presence of nitrogen and oxygen. The capacitance of N-doped ZTC is lower in alkaline electrolyte, probably due to the loss of electrochemical activity of certain oxygen functionalities. Interestingly, the electro-oxidation process of N-ZTC implies lower irreversible currents (providing higher electrochemical stability) than for ZTC. The presence of quaternary nitrogen greatly improves the electric conductivity of N-ZTC, which shows a superior rate performance. ZTC and N-ZTC capacitors were constructed using 1 M H2 SO4 . Under the same conditions, N-doped ZTC based capacitor has higher energy density, 6.7 vs 5.9 W h/kg. The power density of N-ZTC is four times higher, producing an outstanding maximum power of 98 kW/kg. These results provide clear evidences of the advantages of doping advanced porous carbon materials with nitrogen functionalities. Graphical abstract: Image 1